Green and environment-friendly coating fluorescence enhancement method for CdTe QDs through silane surface hyperbranched polymerization modification

The surface modification on CdTe QDs is performed through the silane surface hyperbranching polymerization modification method to form P-APTEs@CdTe QDs composites, which solves the problem of fluorescence intensity and wavelength improvement in the existing technology, and achieves a green and environmentally friendly fluorescence enhancement effect, which improves the Optical properties of quantum dots and application potential of materials.

CN119144319APending Publication Date: 2024-12-17GUANGDONG PHARMA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411129103.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art methods to improve the fluorescence intensity and wavelength of CdTe QDs have high costs, difficult material ratio control, and possible exposure to toxic and harmful substances. It is difficult to develop a green and environmentally friendly and easy-to-operate method to modulate the electronic structure of quantum dots. To obtain a phosphor with higher luminous intensity.

Method used

The silane surface hyperbranched polymerization modification method was used to synthesize stable water-soluble CdTe QDs by solvothermal method, and APTEs were added to the quantum dot aqueous solution for surface modification to form a P-APTEs@CdTe QDs complex to improve fluorescent quantum yield and light response The absorption capacity of quantum dots increases the utilization of short-wave radiation and emits visible light with longer wavelengths.

Benefits of technology

A significant improvement in fluorescence quantum yield was achieved, the composite's absorption capacity of light was greatly enhanced, and the quantum dots showed a narrower half-maximum full width, which improved the monochromaticity of fluorescence and the optoelectron utilization of materials. This method is green and environmentally friendly. , easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144319A_ABST
    Figure CN119144319A_ABST
Patent Text Reader

Abstract

The invention discloses a green and environment-friendly coating fluorescence enhancement method for CdTe QDs by silane surface hyperbranched polymerization modification, which comprises the following steps: synthesizing stable CdTe QDs by using water-soluble 3-MPA as a stabilizer through a simple solvothermal method; a P-APTEs (at) CdTe QDs compound with an ideal fluorescence enhancement effect is obtained by adding a small amount of APTEs into a quantum dot aqueous solution to carry out coating modification on the surfaces of the quantum dots, the fluorescence quantum yield is also obviously improved, the light absorption capacity of the compound is greatly enhanced, the utilization of the quantum dots to short-wave radiation is increased, and the fluorescence enhancement effect of the quantum dots is improved. Compared with the prior art, the CdTe QDs have the advantages that the CdTe QDs are modified, visible light with longer wavelength is emitted, the modified quantum dots show narrower FWHM, the fluorescence monochromaticity is improved, the fluorescence intensity of the modified CdTe QDs is enhanced by 20 times under the optimal effect, and the fluorescence quantum yield is increased by 153.79%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluorescence enhancement, and in particular to a green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane. Background Art

[0002] CdTe QDs is a classic II-VI semiconductor quantum dot with a particle size in the range of 1-10 nanometers. It belongs to zero-dimensional nanomaterials, which are close to or smaller than the exciton Bohr radius. It is an important semiconductor material that can absorb a large amount of visible light and has unique optical properties. CdTe is a p-type semiconductor with a direct band gap and high hole mobility. Because of the extremely small nanometer size, most of the atoms in the quantum dots are in the surface state, and the surface state of the quantum dots has a significant effect on their luminescence effect. Due to the quantum confinement effect, CdTe QDs have a quantized electronic structure, and the luminescence wavelength can be controlled by the particle size. It is usually used as a long-wavelength fluorescence emission quantum dot material. The performance of CdTe QDs is closely related to its lattice constant. The smaller the lattice constant, the larger its band gap, the higher the potential barrier of the electrons that generate voltage, and the stronger the jumping ability of the electrons in the CdTe crystal, thereby increasing the mobility of the electrons in the system. However, as the emission wavelength redshifts, the fluorescence intensity of the quantum dots will gradually weaken, affecting the use effect. Therefore, in order to improve its application performance in the fields of optical detection, biological staining, etc., it is very meaningful to use certain specific methods to increase the fluorescence intensity of quantum dots and obtain quantum dot-modified products with longer wavelength, stronger intensity and purer fluorescence emission.

[0003] Fluorescence enhancement is an eternal theme in the development of fluorescent materials. People have begun to explore the direction of fluorescence enhancement since the discovery of nano-fluorescent materials. The study of fluorescence enhancement has important application value in improving the optical properties of quantum dots, improving the sensitivity of fluorescent probes, and improving the performance of optoelectronic devices. In the past decade, many methods have been developed for quantum dot fluorescence enhancement, including but not limited to heteroatom doping, core-shell heterojunction structure, surface plasmon enhancement, etc., which increase the absorption of light, eliminate non-radiative relaxation or increase the quantum yield to improve the luminescence efficiency of existing quantum dots. However, these methods usually have the problems of high cost, strict material ratio control, and difficult to control conditions, and usually come into contact with more toxic and harmful substances in the subsequent experimental process. It is very necessary to develop a new, simple, green, and easy-to-operate method to modulate the electronic structure of quantum dots to obtain phosphors with higher luminescence intensity.

[0004] Therefore, we propose a green and environmentally friendly method of silane surface hyperbranched polymerization modification to enhance the fluorescence of CdTe QDs to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to provide a green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane. Stable CdTeQDs with water-soluble 3-MPA as a stabilizer are synthesized by a simple solvothermal method, and a P-APTEs@CdTe QDs complex with an ideal fluorescence enhancement effect is obtained by adding a small amount of APTEs to a quantum dot aqueous solution to coat the surface of the quantum dots. The fluorescence quantum yield is also significantly improved, the light absorption capacity of the composite is greatly enhanced, the utilization of short-wave radiation by quantum dots is increased, and visible light with a longer wavelength is emitted. The modified quantum dots show a narrower full width at half maximum (FWHM), and the fluorescence monochromaticity is improved, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] A green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane, comprising:

[0008] S1. Synthesis of CdTe QDs: CdTe QDs were synthesized by hydrothermal method;

[0009] S2. Polymerization of hyperbranched polysiloxane on the surface of quantum dots.

[0010] Further, CdTe QDs are synthesized by a hydrothermal method, comprising:

[0011] (1) Prepare a precursor solution of Cd and a precursor solution of Te respectively, take 0.3-0.8 mmol of Te powder and 1.0-2.4 mmol of NaBH4, the molar ratio of Te powder to NaBH4 is 1:3, disperse them in 8-12 ml of deoxygenated deionized water, and protect them in a N2 atmosphere, stir and heat them in a 35-45°C water bath for 30-50 minutes until the solution becomes clear and transparent purple; take 0.3-0.8 mmol of CdCl2, disperse it in 15-40 ml of deionized water, add 0.8-1.2 mmol of acidic stabilizer, and then use 1 mol / L NaOH to adjust the pH value of the solution to 9.0;

[0012] (2) The obtained Cd precursor solution is also protected under N2 atmosphere, and 3-5 ml of clear Te precursor solution is quickly added to 15-25 ml of Cd precursor solution. The volume ratio of Te precursor solution to Cd precursor solution is 1:5. Reflux at 90-105°C under N2 protection and heat for 5-7 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 55-65°C for use.

[0013] Further, CdTe QDs are synthesized by a hydrothermal method, comprising:

[0014] (1) Prepare Cd precursor solution and Te precursor solution respectively, take 0.5 mmol Te powder and 1.5 mmol NaBH4, disperse them in 10 ml deoxygenated deionized water, and protect them in N2 atmosphere, stir and heat in a 40°C water bath for 40 minutes until the solution becomes clear and transparent purple; take 0.5 mmol CdCl2, disperse it in 25 ml deionized water, add 1 mmol acid stabilizer, and then use 1 mol / L NaOH to adjust the pH value of the solution to 9.0;

[0015] (2) The obtained Cd precursor solution is also protected under N2 atmosphere, and 4 ml of clear Te precursor solution is quickly added to 20 ml of Cd precursor solution, refluxed at 100°C under N2 atmosphere, and heated for 6 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 60°C for use.

[0016] Furthermore, the acidic stabilizer is 3-MPA, and 3-MPA is mercaptopropionic acid.

[0017] Furthermore, the acidic stabilizer is thioglycolic acid.

[0018] Furthermore, the acidic stabilizer is cysteine.

[0019] Furthermore, the synthesized quantum dots are dispersed in an aqueous solution of 0.8-1.2 mg / 1 ml, and aminosilane is added at room temperature. Aminosilane can be rapidly cross-linked and polymerized in the aqueous solution under the catalysis of its own amino group. The solution is oscillated at room temperature for 8-15 minutes to obtain silane-modified quantum dots with stable fluorescence enhancement effect.

[0020] Furthermore, the synthesized quantum dots were dispersed in an aqueous solution of 1 mg / 1 ml, and aminosilane was added at room temperature. Aminosilane can be rapidly cross-linked and polymerized in the aqueous solution under the catalysis of its own amino group. The solution was oscillated at room temperature for 10 minutes to obtain silane-modified quantum dots with stable fluorescence enhancement effect.

[0021] Furthermore, the aminosilane is APTEs, and APTEs is triaminopropyltriethoxysilane.

[0022] Furthermore, the aminosilane is DAMO, and DAMO is N-[3-(trimethoxysilyl)propyl]ethylenediamine.

[0023] Furthermore, the present invention can also be applied to the fluorescence enhancement of CdS quantum dots and CdSe quantum dots having similar surfaces.

[0024] Compared with the prior art, the advantages of the present invention are:

[0025] The present invention synthesizes stable water-soluble CdTe QDs with 3-MPA as a stabilizer by a simple solvent thermal method, and obtains a P-APTEs@CdTe QDs complex with an ideal fluorescence enhancement effect by adding a small amount of APTEs to a quantum dot aqueous solution to modify the surface of the quantum dot coating. The fluorescence quantum yield is also significantly improved, the light absorption capacity of the complex is greatly enhanced, the quantum dots increase the utilization of short-wave radiation, and emit visible light with a longer wavelength. The modified quantum dots show a narrower FWHM, and the fluorescence monochromaticity is improved. Due to the presence of the acidic surface ligands of the quantum dots and the characteristics of aminosilane self-catalytic polymerization, APTEs can be easily bonded to the surface of the quantum dots at room temperature and self-polymerized to form a hyperbranched polymer, which is cross-linked to form a film attached to the surface of the quantum dots. It is a green and environmentally friendly method that is easy to operate.

[0026] The present invention has obvious fluorescence enhancement effect on CdS and CdSe quantum dots synthesized in water solvents with acidic group-stabilized surfaces, and has a wide range of expansion space. The fluorescence enhancement of quantum dots is due to the presence of the surface Si iOS i, SiN-Si cross-polymer layer to form a core-shell structure of P-APTEs@CdTe. The surface silane polymer has a large band gap, and the photoelectron transfer between the two closely connected systems is significant. The high-energy photoelectrons replace the low-energy photoelectrons through N→S→Cd between the systems, which improves the effective photoelectron utilization of fluorescent materials, and the presence of the conjugated structure of the silane polymer on the surface of the quantum dots enhances the absorption of light. The problem of low utilization rate of short-wavelength light by long-wavelength emission quantum dots is improved, and the electron transfer within the system also indicates the improvement of the potential photocatalytic ability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 In the figure, (A) and (B) are the fluorescence enhancement effect diagrams of P-APTEs@CdTe QDs;

[0029] Figure 2 In the figure, (A) and (B) are the fluorescence quantum yield diagrams of CdTe QDs and P-APTEs@CdTe QDs, respectively;

[0030] Figure 3In the figure, (A) fluorescence emission changes of CdTe QDs after adding APTEs over time; (B) fluorescence absorption changes of CdTe QDs after adding APTEs over time; (C) fluorescence enhancement effect diagram when supersaturated APTEs are added;

[0031] Figure 4 (A) Fluorescence enhancement effect of P-APTEs@CdTe QDs under different excitation wavelengths; (B) Fluorescence emission changes of CdTe QDs after adding APTEs;

[0032] Figure 5 (A) Changes in the half-peak width of CdTe QDs after adding 0-300u lAPTEs; (B) Changes in the half-peak width when equal amounts of APTEs are added to the quantum dot solution and incubated at different temperatures;

[0033] Figure 6 The UV absorption diagram of CdTe QDs surface before and after silane hyperbranched polymerization modification and P-APTEs;

[0034] Figure 7 (A) Lattice spacing of CdTe QDs; (B) Lattice spacing of P-APTEs@CdTe QDs; (C) Particle size distribution of CdTe QDs; (D) Particle size distribution of P-APTEs@CdTe QDs. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the present invention is described in detail with reference to the schematic diagram. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagram showing the device structure will not be partially enlarged according to the general scale, and the schematic diagram is only an example, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional space dimensions of length, width and depth should be included.

[0038] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0039] A green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane, comprising:

[0040] S1. Synthesis of CdTe QDs: CdTe QDs are synthesized by a hydrothermal method, including:

[0041] (1) Prepare a precursor solution of Cd and a precursor solution of Te respectively, take 0.3-0.8 mmol of Te powder and 1.0-2.4 mmol of NaBH4, the molar ratio of Te powder to NaBH4 is 1:3, disperse them in 8-12 ml of deoxygenated deionized water, and protect them in a N2 atmosphere, stir and heat them in a 35-45°C water bath for 30-50 minutes until the solution becomes clear and transparent purple; take 0.3-0.8 mmol of CdCl2, disperse it in 15-40 ml of deionized water, add 0.8-1.2 mmol of acidic stabilizer, and then use 1 mol / L NaOH to adjust the pH value of the solution to 9.0;

[0042] (2) The obtained Cd precursor solution is also protected under a N2 atmosphere, and 3-5 ml of a clear Te precursor solution is quickly added to 15-25 ml of a Cd precursor solution, with the volume ratio of the Te precursor solution to the Cd precursor solution being 1:5. The solution is refluxed at 90-105°C under the protection of a N2 atmosphere and heated for 5-7 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 55-65°C for later use; wherein the acidic stabilizer is 3-MPA.

[0043] S2. Polymerization of hyperbranched polysiloxane on the surface of quantum dots. The synthesized quantum dots are dispersed in an aqueous solution of 0.8-1.2 mg / 1 ml. Aminosilane is added at room temperature. Aminosilane can be catalyzed by its own amino group in the aqueous solution and rapidly cross-linked and polymerized. The mixture is oscillated at room temperature for 8-15 minutes to obtain silane-modified quantum dots P-APTEs@CdTeQDs with stable fluorescence enhancement effect, where the aminosilane is APTEs.

[0044] Embodiment 1

[0045] A green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane, comprising:

[0046] S1. Synthesis of CdTe QDs: CdTe QDs are synthesized by a hydrothermal method, including:

[0047] (1) Prepare the precursor solution of Cd and the precursor solution of Te respectively. Take 0.5 mmol Te powder and 1.5 mmol NaBH4, disperse them in 10 ml deoxygenated deionized water, and protect them in N2 atmosphere. Stir and heat them in a 40°C water bath for 40 minutes until the solution becomes clear and transparent purple. Take 0.5 mmol CdCl2, disperse it in 25 ml deionized water, add 1 mmol 3-MPA, and then adjust the pH value of the solution to 9.0 with 1 mol / L NaOH.

[0048] (2) The obtained Cd precursor solution is also protected under N2 atmosphere, and 4 ml of clear Te precursor solution is quickly added to 20 ml of Cd precursor solution, and refluxed at 100 ° C under N2 atmosphere for 6 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 60 ° C for use;

[0049] S2. Take a 1 mg / 1 ml aqueous solution of the synthesized quantum dots and add APTEs at room temperature. APTEs can be catalyzed by its own amino group in the aqueous solution and rapidly cross-link and polymerize. Oscillate at room temperature for 10 minutes to obtain silane-modified quantum dots P-APTEs@CdTe QDs with stable fluorescence enhancement effect.

[0050] Embodiment 2

[0051] A green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane, comprising:

[0052] S1. Synthesis of CdTe QDs: CdTe QDs are synthesized by a hydrothermal method, including:

[0053] (1) Prepare Cd precursor solution and Te precursor solution respectively, take 0.4 mmol Te powder and 1.2 mmol NaBH4, disperse them in 8 ml deoxygenated deionized water, and protect them in N2 atmosphere, stir and heat in a water bath at 35-45°C for 40 minutes until the solution becomes clear and transparent purple; take 0.4 mmol CdCl2, disperse it in 20 ml deionized water, add 0.8 mmol 3-MPA, and then adjust the pH value of the solution to 9.0 using 1 mol / L NaOH;

[0054] (2) The obtained Cd precursor solution is also protected under N2 atmosphere, and 3 ml of clear Te precursor solution is quickly added to 15 ml of Cd precursor solution, and refluxed at 100 ° C under N2 atmosphere for 5.5 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 60 ° C for use;

[0055] S2. Polymerization of hyperbranched polysiloxane on the surface of quantum dots. The synthesized quantum dots were dispersed in an aqueous solution of 0.8 mg / 1 ml. APTEs were added at room temperature. APTEs can be catalyzed by its own amino group in the aqueous solution and rapidly cross-linked and polymerized. The solution was oscillated at room temperature for 8 minutes to obtain silane-modified quantum dots P-APTEs@CdTe QDs with stable fluorescence enhancement effect.

[0056] Embodiment 3

[0057] A green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane, comprising:

[0058] S1. Synthesis of CdTe QDs: CdTe QDs are synthesized by a hydrothermal method, including:

[0059] (1) Prepare the precursor solution of Cd and the precursor solution of Te respectively. Take 0.8 mmol Te powder and 2.4 mmol NaBH4, disperse them in 12 ml deoxygenated deionized water, and protect them in N2 atmosphere. Stir and heat them in a 40°C water bath for 45 minutes until the solution becomes clear and transparent purple. Take 0.6 mmol CdCl2, disperse it in 35 ml deionized water, add 1.2 mmol 3-MPA, and then adjust the pH value of the solution to 9.0 with 1 mol / L NaOH.

[0060] (2) The obtained Cd precursor solution is also protected under N2 atmosphere, and 5 ml of clear Te precursor solution is quickly added to 25 ml of Cd precursor solution, and refluxed at 100 ° C under N2 atmosphere for 6 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 60 ° C for use;

[0061] S2. Polymerization of hyperbranched polysiloxane on the surface of quantum dots. The synthesized quantum dots were dispersed in an aqueous solution of 1.2 mg / 1 ml. APTEs were added at room temperature. APTEs can be rapidly cross-linked and polymerized in the aqueous solution under the catalysis of its own amino group. The solution was oscillated at room temperature for 12 minutes to obtain silane-modified quantum dots P-APTEs@CdTe QDs with stable fluorescence enhancement effect.

[0062] Experimental example

[0063] 1. Reagents and instruments

[0064] 1.1 Reagents

[0065] Te powder, mercaptopropionic acid, thioglycolic acid, cysteine, sodium hydroxide, 3-aminopropyltriethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine, all reagents were of commercial analytical grade and did not require further purification before use. All laboratory water was double distilled water.

[0066] 1.2 Instruments

[0067] Fluorescence spectrometer (SH I MADZU RF-5301PC, Japan); UV-visible spectrometer (SH IMADZUS UV-2550, Japan); steady-state / transient fluorescence spectrometer (ED I NBURGH FLS1000, UK); transmission electron microscope (FE I Ta l os F200x, USA).

[0068] Second, experimental verification was carried out from the aspects of fluorescence enhancement effect, UV analysis and XRD analysis (the P-APTEs@CdTe QDs prepared in Example 1 were used as samples for the experiment)

[0069] 2.1 Fluorescence enhancement effect

[0070] Firstly, fluorescence spectroscopy was used to analyze the fluorescence enhancement effect of silane on quantum dots ( Figure 1 A, 1B). In the best enhanced state, CdTe QDs can achieve a 20-fold fluorescence enhancement effect in solution, and even in the solid state, there is a significant fluorescence enhancement effect ( Figure 1 B). APTEs enhances the fluorescence intensity of quantum dots with high efficiency in small amounts, and the optimal effect is achieved at 3μl / ml. Under 365nm wavelength light excitation, the fluorescence quantum yield increases by 153.79% ( Figure 2 shown).

[0071] After silane is added to the solution, the fluorescence of the quantum dots is enhanced along with the self-polymerization of silane. The fluorescence of the quantum dots is not enhanced immediately due to the surface reaction after the addition of silane. The enhancement process of the material's light absorption and emission is consistent with the silane polymerization process ( Figure 3 A, 3B), indicating that the fluorescence enhancement effect is related to the formation of the silane hyperbranched polymer layer. And as the amount of silane added continues to increase, the fluorescence enhancement effect of the system does not change significantly, which shows that the subsequent addition of excess silane has no positive effect on the effective fluorescence enhancement effect of the silane surface shell. This may be because the ligands on the surface of the quantum dots are densely distributed, resulting in a relatively large aggregation density of the silane layer closest to the quantum dots, a higher charge density, a stronger conjugation effect, and a closer distance to the quantum dots. The subsequent layers are affected by the alkylamino chains of APTEs themselves, and the polymerization structure is looser, no effective conjugation structure is formed, and the light absorption capacity decreases, which is manifested as a weak fluorescence enhancement effect. And the fluorescence absorption peak of the silane polymer is located at the excitation peak position given by us, and the fluorescence internal rate effect will also affect the fluorescence intensity of the system.

[0072] Then the fluorescence enhancement effect under different excitation wavelengths was tested ( Figure 4 A), showing that the material has a large enhancement factor under 360nm light excitation, which is consistent with the maximum absorption peak position of P-APTEs ( Figure 4 (As shown in B), it shows that there is obvious excited state energy transfer in the system.

[0073] The fluorescence half-peak width is an important physical property to measure the fluorescence monochromaticity of quantum dots. It is of great significance to the application of quantum dots. By analyzing the fluorescence half-peak width under the addition amount of 0-300 μ l, we found that the modified quantum dots have a significant decrease in half-peak width ( Figure 5 A), effectively improving the fluorescence monochromaticity, and the sharpening effect of the half-peak width is almost unaffected by the reaction temperature, and is easy to operate ( Figure 5 B).

[0074] 2.2 UV analysis

[0075] The optical absorption properties of CdTe QDs, P-APTEs and P-APTEs@CdTe QDs colloids were characterized using a UV-visible spectrometer. The UV absorption spectra of quantum dots before and after the addition of APTEs and P-APTEs were measured at the same basic quantum dot concentration, conversion wavelength and slit ( Figure 6 As shown in Figure 2). First, the absorption spectrum of CdTe QDs shows a weak absorption peak at about 495 nm, which matches the signal of CdTe QDs observed in the solution phase in the literature

[21] . The silane self-polymer alone is almost colorless and transparent in aqueous solution, without a unique coefficient. Therefore, we can infer from the absorption data that the broad absorption enhancement of the modified quantum dots is not due to the inert background provided by P-APTEs for CdTe quantum dots, but can be attributed to the relative increase in the particle size of the CdTe nanoparticles coated with P-APTEs and the formation of a new conjugated structure on the surface. The addition of excess APTEs only leads to a slight enhancement of the ultraviolet absorption of P-APTEs@CdTe QDs, and there is no significant change in the fluorescence intensity, which also verifies the inference of the fluorescence enhancement mechanism.

[0076] 2.3 XRD analysis

[0077] Transmission electron microscopy images ( Figure 7) shows that the original CdTe QDs of the same concentration have a high dispersion under HRTEM, with an average particle size of 3.4697nm. After modification with APTEs, the particle size of the quantum dots increases by an average of about 0.42nm. This is due to the growth of silane hyperbranched polymers on the surface of the quantum dots, which may be the reason for the red shift of the fluorescence emission of the quantum dots. The distribution of the modified quantum dots becomes more concentrated, and the quantum dots are concentrated in a huge micelle and dispersed more evenly. This is because silane plays the role of filler between quantum dots in the subsequent polymerization, so that the quantum dots are connected by loose silane polymers, which are relatively more fixed in space. A very small number of quantum dots have adhesion, forming a polymer with a larger diameter. This effect can be reduced by accelerating stirring during the modification process. The lattice constants of the quantum dots before and after modification do not change significantly, averaging 0.2156nm and 0.2172nm, respectively, corresponding to the (220) crystal plane of the CdTe crystal. The smaller lattice means that it has a better photoelectric effect. Combined with XPS and ultraviolet peak position, it is confirmed that it is a zinc blende CdTe crystal.

[0078] The experimental results show that the mechanism of fluorescence enhancement on the silane surface is related to the modification of surface defects of quantum dots and the electron transfer within the system. The modified quantum dots have a stronger light capture ability due to the conjugated structure produced by the surface connection of P-APTEs. This method can not only achieve excellent fluorescence enhancement effect, but also protect the quantum dot material, so that the fluorescence intensity of the quantum dots remains almost unchanged for a long time. A high-speed electron transfer pathway of N→S→Cd based on the structure is proposed, which promotes electron transfer within the system. The modified quantum dots have higher short-wave excitation fluorescence intensity and longer wavelength light emission, which significantly enhances the advantages of quantum dots such as CdTe QDs, CdS QDs, and CdSe QDs as photoelectric sensors, and has broad application prospects.

[0079] Working principle of the present invention:

[0080] The unconventional fluorescence of silane hyperbranched polymers has long been discovered by researchers as an aggregation-induced fluorescence (AIE) phenomenon. The self-polymerization of APTEs in solution is mainly through the dehydration polymerization of Si-OH bonds after the hydrolysis of aminosilane molecules to form SiO-Si covalent bonds that are interconnected to form a hyperbranched polysiloxane network. In space, due to the excellent flexibility of the siloxane chain, N-Si bonds are formed. The complex spatial structure of hyperbranched polysiloxane causes electron-rich atoms to aggregate through spatial conjugation. Due to the relatively rigid structure of the polymer, the aggregation-induced effect produces fluorescence, and the fluorescence intensity increases within a certain range as the concentration in the polymer solution increases. This unconventional fluorescent product of silane can be spontaneously generated under appropriate conditions and has a high fluorescence quantum yield. The unique characteristics of the unconventional luminescence of APTEs hyperbranched polymers make them very suitable for auxiliary ligands for luminescent materials.

[0081] Due to the presence of electron-rich P-APTEs tightly connected on the surface, P-APTEs generate a large number of photogenerated electrons under photoexcitation. Since there is obvious charge transfer inside P-APTEs themselves, when they are tightly connected with CdTe QDs, the photogenerated electrons are transmitted at high speed to the surface of the quantum dots along the electron channel of N→S→Cd. Since CdTe QDs are a p-type semiconductor with a direct band gap and high hole mobility, the holes inside the material are mainly concentrated on the surface of the quantum dots during excitation. The photogenerated electrons of the quantum dots need to be transferred from the center of the quantum dots to the surface of the quantum dots to combine with the holes. The spatial transmission distance of the electrons is farther than the distance between the surface P-APTEs and the surface of CdTe QDs, resulting in the advantage of the photogenerated electrons of P-APTEs combining with the holes on the surface of the quantum dots, completing the replacement of low-energy photons with high-energy photons, returning to the ground state to produce fluorescence, effectively improving the influence of internal defects of the quantum dots on the electrons during transmission, and greatly improving the fluorescence effect of the quantum dots. Under the irradiation of ultraviolet excitation light, the electrons on the VB of P-APTEs@CdTe QDs are excited into the CB. Then, the photoinduced electrons flow from the electron donor to the acceptor, resulting in the spatial separation of the electrons and holes of P-APTEs, and the recombination of charge carriers is significantly reduced due to the electron transfer, which manifests as the quenching of fluorescence. At the same time, the DA structure greatly expands the photoresponse area of ​​​​P-APTEs@CdTe QDs and improves the efficiency of light utilization. In addition, P-APTEs forms a wide bandgap shell on the surface of quantum dots, which effectively eliminates the surface defects of quantum dots and synergistically enhances fluorescence.

[0082] The present invention synthesizes stable, water-soluble CdTe QDs with 3-MPA as a stabilizer by a simple solvothermal method, and obtains a P-APTEs@CdTe QDs complex with an ideal fluorescence enhancement effect by adding a small amount of APTEs to a quantum dot aqueous solution to modify the surface of the quantum dot coating. The fluorescence quantum yield is also significantly improved, and the light absorption capacity of the complex is greatly enhanced, which increases the utilization of short-wave radiation by the quantum dots and emits visible light with a longer wavelength. The modified quantum dots show a narrower FWHM and improve the fluorescence monochromaticity. Due to the presence of the acidic surface ligands of the quantum dots and the characteristics of aminosilane self-catalytic polymerization, APTEs can be easily bonded to the surface of the quantum dots at room temperature and cross-linked to form a film attached to the surface of the quantum dots, and self-polymerize to form a hyperbranched polymer, which is a green, environmentally friendly and easy-to-operate method. This method has a significant fluorescence enhancement effect on CdS and CdSe quantum dots synthesized in an aqueous solvent with acidic group-stabilized surfaces, and has a wide range of expansion space. The fluorescence enhancement of quantum dots is due to the presence of Si-O-Si and SiN-Si cross-polymer layers on the surface, which form a core-shell structure of P-APTEs@CdTe. The surface silane polymer has a large band gap, and the photoelectron transfer between the two closely connected systems is significant. The high-energy photoelectrons replace the low-energy photoelectrons through N→S→Cd between the systems, which improves the effective photoelectron utilization of fluorescent materials. In addition, the presence of the conjugated structure of the silane polymer on the surface of the quantum dots enhances the absorption of light. The problem of low utilization of short-wavelength light by long-wavelength emission quantum dots is improved, and the electron transfer within the system also indicates the improvement of the potential photocatalytic ability of the material.

[0083] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization of silane, characterized in that: include: S1. Synthesis of CdTe QDs: CdTe QDs were synthesized by hydrothermal method; S2. Polymerization of hyperbranched polysiloxane on the surface of quantum dots.

2. The green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization of silane according to claim 1, characterized in that: CdTe QDs were synthesized using a hydrothermal method, including: (1) Prepare a precursor solution of Cd and a precursor solution of Te respectively, take 0.3-0.8 mmol of Te powder and 1.0-2.4 mmol of NaBH4, the molar ratio of Te powder to NaBH4 is 1:3, disperse them in 8-12 ml of deoxygenated deionized water, and protect them in a N2 atmosphere, stir and heat them in a 35-45°C water bath for 30-50 minutes until the solution presents a clear and transparent purple color; take 0.3-0.8 mmol of CdCl2, disperse it in 15-40 ml of deionized water, add 0.8-1.2 mmol of an acidic stabilizer, and then use 1 mol / L NaOH to adjust the pH value of the solution to 9.0; (2) The obtained Cd precursor solution is also protected under N2 atmosphere, and 3-5 ml of clear Te precursor solution is quickly added to 15-25 ml of Cd precursor solution. The volume ratio of Te precursor solution to Cd precursor solution is 1:

5. Reflux at 90-105°C under N2 protection and heat for 5-7 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 55-65°C for use.

3. The green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane according to claim 2, characterized in that: CdTe QDs were synthesized using a hydrothermal method, including: (1) Prepare Cd precursor solution and Te precursor solution respectively, take 0.5 mmol Te powder and 1.5 mmol NaBH4, disperse them in 10 ml deoxygenated deionized water, and protect them in N2 atmosphere, stir and heat in a 40°C water bath for 40 minutes until the solution becomes clear and transparent purple; take 0.5 mmol CdCl2, disperse it in 25 ml deionized water, add 1 mmol acid stabilizer, and then use 1 mol / L NaOH to adjust the pH value of the solution to 9.0; (2) The obtained Cd precursor solution is also protected under N2 atmosphere, and 4 ml of clear Te precursor solution is quickly added to 20 ml of Cd precursor solution, refluxed at 100°C under N2 atmosphere, and heated for 6 hours to obtain CdTe QDs; CdTe QDs are precipitated and washed with anhydrous ethanol, and dried at 60°C for use.

4. The green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane according to claim 2, characterized in that: The acidic stabilizer is 3-MPA.

5. The green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane according to claim 1, characterized in that: In S2, the synthesized quantum dots are dispersed in an aqueous solution of 0.8-1.2 mg / 1 ml, and aminosilane is added at room temperature. Aminosilane can be catalyzed by its own amino group in the aqueous solution to rapidly cross-link and polymerize. The mixture is shaken at room temperature for 8-15 minutes to obtain silane-modified quantum dots with stable fluorescence enhancement effect.

6. The green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane according to claim 5, characterized in that: In S2, the synthesized quantum dots are dispersed in an aqueous solution of 1 mg / 1 ml, and aminosilane is added at room temperature. Aminosilane can be catalyzed by its own amino group in the aqueous solution to rapidly cross-link and polymerize. The solution is oscillated at room temperature for 10 minutes to obtain silane-modified quantum dots with stable fluorescence enhancement effect.

7. The green and environmentally friendly method for enhancing the fluorescence of CdTe QDs by surface hyperbranched polymerization modification of silane according to claim 5, characterized in that: The aminosilane is APTEs or DAMO.